Kajian Filosofis Kompetensi Multikulturalisme Guru sebagai Landasan Peningkatan SDM Pendidikan - Nadia Salsabila; Bambang Yulianto; Dewi Fitrotus Sadiyah (Jurnal Pendidikan dan Kewarganegara Indonesia, 2026)
Multicultural competence refers to an individual's capacity to navigate and value the diversity within their environment. This skill is essential for all strata of Indonesian society, given Indonesia's diversity in ethnicities, cultures, languages, and faiths. Teachers occupy a pivotal role in fostering multicultural competency within society, as they engage directly with pupils on a regular basis. Teacher intercultural competency has three primary dimensions: knowledge, attitudes, and skills. Multicultural knowledge can be acquired through multiple avenues, including formal education, specialised training, or firsthand experience with varied populations. Multicultural education seeks to equip students with an awareness of the complexities of variety in society, enabling them to coexist amicably. The fundamental principles of multicultural education encompass equality, democracy, pluralism, and tolerance. Educators, as pivotal participants in the educational process, are anticipated to comprehend multicultural values conceptually and to incorporate them into everyday instructional activities. Consequently, the multicultural competency of educators may cultivate students who are not only academically proficient but also possess an inclusive mindset, value diversity, and are prepared to engage in a pluralistic society.